2019
DOI: 10.1016/j.jclepro.2019.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on marine LNG propulsion systems for LNG carriers through an enhanced hybrid decision making model

Abstract: Since the use of LNG as an alternative fuel has drawn increasing attention from the marine industry, this paper aimed to evaluate three competitive LNG fuelled engine systems: ultrasteam turbine, four-stroke medium speed engine, and two-stroke low-speed engine systems. To achieve this goal, the paper developed an enhanced hybrid decision-making model which was applied to integrate the economic, environmental and technical performance of these systems. This model can be represented as a semi-quantitative multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In addition, it is worth noting that this paper does not present emission levels at each life stage of scrubber systems. One of reasons is that a series of past research has demonstrated that the operating phase of the marine systems has the greatest contribution (as high as 99%) to the overall environmental impacts (Jeong et al, 2019). It is because the operating phase has much extensive energy consumption and longer service time compared to construction, maintenance and scrapping.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is worth noting that this paper does not present emission levels at each life stage of scrubber systems. One of reasons is that a series of past research has demonstrated that the operating phase of the marine systems has the greatest contribution (as high as 99%) to the overall environmental impacts (Jeong et al, 2019). It is because the operating phase has much extensive energy consumption and longer service time compared to construction, maintenance and scrapping.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the primary goal of this LCA research, it adopted the life cycle of energy pathways consisting of the production, the transport and the use stages (see Figure 6). The scope of analysis was not extended to battery or diesel engine products for the reason that a series of previous LCA studies have proven that the environmental impacts relative to manufacturing, installing and recycling of marine products to be negligibly small [7,28,29]. Figure 7 shows the overview of the LCA process for this study.…”
Section: Goal and Scopementioning
confidence: 99%
“…(c) Use stageThe use stage describes a way of estimating the emissions associated with the on-board use. For the past maritime LCA research, engine emissions were calculated based on the emission factors provided by the IMO[7,8,28,29,33,34]. It was noticed that such an analytical calculation would probably lead to high discrepancies between the actual and calculated emissions[14,35].…”
mentioning
confidence: 99%
“…Hua et al [22] analyzed the total life cycle emissions of a post-Panamax container ship running in both HFO and natural gas. Jeong et al [23] presented the excellence of using LNG-fueled engines based on economic and environmental viewpoints. In the research, the life cycle cost assessment (LCCA) was advised as a useful tool for decision making across industries.…”
Section: Literature Reviewmentioning
confidence: 99%